Experience Reduces Surgical and Hardware-Related Complications of Deep Brain Stimulation Surgery: A Single-Center Study of 181 Patients Operated in Six Years. (22nd July 2018) - Sorar, Mehmet; Hanalioglu, Sahin; Kocer, Bilge; Eser, Muhammed Taha; Comoglu, Selim Selcuk; Kertmen, Hayri
Abstract : Objective . Deep brain stimulation (DBS) surgery has increasingly been performed for the treatment of movement disorders and is associated with a wide array of complications. We aimed to present our experience and discuss strategies to minimize adverse events in light of this contemporary series and others in the literature. Methods . A retrospective chart review was conducted to collect data on age, sex, indication, operation date, surgical technique, and perioperative and late complications. Results . A total of 181 patients (113 males, 68 females) underwent DBS implantation surgery (359 leads) in the past six years. Indications and targets were as follows: Parkinson's disease (STN) (n = 159 ), dystonia (GPi) (n = 13 ), and essential tremor (Vim) (n = 9 ). Mean age was 55.2 ± 11.7 (range 9–74) years. Mean follow-up duration was 3.4 ± 1.6 years. No mortality or permanent morbidity was observed. Major perioperative complications were confusion (6.6%), intracerebral hemorrhage (2.2%), stroke (1.1%), and seizures (1.1%). Long-term adverse events included wound (7.2%), mostly infection, and hardware-related (5.5%) complications. Among several factors, only surgical experience was found to be related with overall complication rates (early period: 31% versus late period: 10%;p = 0.001 ). Conclusion . The rates of both early and late complications of DBS surgery are acceptably low and decrease significantly with cumulative experience.